Immigrant Faith : Patterns of Immigrant Religion in the United States, Canada, and Western Europe - Connor, Phillip, 1976- (Book collections on Project MUSE., 2014)
"Immigrant Faith examines trends and patterns relating to religion in the lives of immigrants. The volume moves beyond specific studies of particular faiths in particular immigrant destinations to present the religious lives of immigrants in the United States, Canada, and Europe on a broad scale. Religion is not merely one aspect among many in immigrant lives. Immigrant faith affects daily interactions, shapes the future of immigrants in their destination society, and influences society beyond the immigrants themselves. In other words, to understand immigrants, one must understand their faith. Drawing on census data and other surveys, including data sources from several countries and statistical data from thousands of immigrant interviews, the volume provides a concise overview of immigrant religion. It sheds light on whether religion shapes the choice of destination for migrants, if immigrants are more or less religious after migrating, if religious immigrants have an easier adjustment, or if religious migrants tend to fare better or worse economically than non-religious migrants. Immigrant Faith covers demographic trends from initial migration to settlement to the transmission of faith to the second generation. It offers the perfect introduction to big picture patterns of immigrant religion for scholars and students, as well as religious leaders and policy makers"--